Footwear preferences among emergency and outpatient nurses: Implications for preventing work-related musculoskeletal disorders - Fitria, Nita; Karisa, Putri; Oktaviana, Mariska; Salimah, Yasmin; Lailannufa, Zannuba; Azzahra, Shifa Leviyanti; Apriandini, Septiani Nur; Sulaeman, Nadila Afifah (The Journal of Palembang Nursing Studies, 2025)
Background: Nurses engage in physically demanding activities that increase the risk of work-related musculoskeletal disorders (WRMSDs). Appropriate footwear selection is an important preventive strategy. Objective: This study aimed to identify and compare footwear preferences between nurses working in the emergency installation (EI) and outpatient installation (OI). Methods: A descriptive quantitative study was conducted with a population of 158 nurses from a public hospital in Indonesia, comprising 93 EI nurses and 65 OI nurses. Using purposive sampling, 125 nurses participated. Data were collected through a structured questionnaire and analyzed descriptively. Results:The most frequently selected footwear characteristics were comfort and cushioning (108 nurses, 44.4%), appropriate size (106 nurses, 41.6%), and durability for daily activities (104 nurses, 35.3%). Notable differences emerged between groups. Outpatient installation (OI) nurses placed greater emphasis on design (43.3%), cushioning (87.9%), weather resistance (65.2%), and foot protection (65.2%) compared with emergency installation (EI) nurses (33.3%, 84.7%, 59.3%, and 62.7%, respectively). Conversely, EI nurses demonstrated a stronger preference for high-quality, higher-priced footwear (72.4%) than OI nurses (47.2%). Conclusion: Nurses prioritize footwear that fits well, is comfortable, cushioned, safe, durable, and reasonably priced. While cushioning and comfort emerged as the most important factors overall, differences in preferences between EI and OI nurses highlight the need for occupational health policies that consider unit-specific requirements. Promoting appropriate footwear may help reduce WRMSD risk and improve nurse well-being.